Organic Acids Metabolic Response and Transcription Factor Expression Changes of Highland Barley Seedlings Under Na2SeO3 Treatment - Xiaozhuo Wu; Huichun Xie; Jianxia Ma; Guigong Geng; Xiaoli Yang; Feng Qiao (Agriculture, 2025)
Selenium (Se), as a vital trace element, plays an important role in regulating the antioxidant systems of plants, strengthening photosynthetic capacity, and enhancing their stress resistance. Selenate and selenite are the dominant forms of Se available to plants in soils. This research takes highland barley as the research object, aiming to assess the impacts of plant growth, organic acid metabolite, and six transcription factor families in highland barley seedlings under varying concentrations of Na2SeO3. The study indicated that compared to the control group (CK), the plant height of highland barley seedlings under Se1 (0.02 g/kg Na2SeO3) treatment significantly increased by 66%. Under the Se2 (0.2 g/kg Na2SeO3) treatment, plant height significantly decreased by 28%. With Na2SeO3 concentration increased, the pigment content, O2− production rate, and soluble protein content in highland barley seedlings decreased, while the contents of soluble sugar, MDA, and H2O2 increased. Se1 treatment was found to be more beneficial for the growth and development of seedlings. The organic selenium in leaves and roots under Se2 treatment significantly increased by 1105-fold and 188-fold, respectively. The most effective migration capability from soil to leaf under Se1 or Se2 treatment was up to 6.15 or 6.56, respectively. Based on metabolomics, 30 differential metabolites of organic acids were screened from highland barley seedlings under Na2SeO3 treatment and showed positive correlationships with organic selenium, inorganic selenium, and total selenium in highland barley seedling leaves. Through transcriptome analysis, heatmap analysis on six major categories of transcription factors (bHLH, MYB, NAC, WRKY, GATA, and HSF) was performed. Under Se2 treatment, approximately two-thirds of the transcription factors showed high expressions. We further screened 26 differentially expressed genes (DEGs) related to Na2SeO3 concentration. Based on correlation analysis, there were six genes in the bHLH family, five in MYB, three in NAC, five in WRKY, and three in the GATA and HSF families that showed positive correlations with 30 differential organic acid metabolites. These results enhance our understanding of the relationship between the organic acid metabolites and transcription factor expression in highland barley seedlings under Na2SeO3 treatment.